IMPROVE THE QUAIITY OF ENVIRONMENT AGRICUITURAI EXTENSION SYSTEM THE PROVINCES OF CENTRAL REGLON OF IRAQ - & AL – Mashhadany, AL-raghi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research aimed at explorivg the reality of environmental agricultural extension system and visualiz proposal to improve the quality agricultural extension systemcontaining the environmental agricltural extension inputs , operations outputs and Continuou improvemen .The research community included the provinces of the central regionof Iraq 8 Provinces where the number of employees 186 respondents Anbar and Salah Religion excluded because of the security conditions at the time of data collection, and thus the research community became (6)Provinces A random sample of (70%) was take by 4 governorates Baghdad,Najaf supervision , Karbala , Babil) ,due to the small number of workers in the provinces covered by the research, a whole community was taken of 148 respondents To achieve research objective questionnaire designed to collect data from respondents consisted of Fenta scale including 89 paragraphs were distributed among four field , including 28 inputs and 39 operation , and 16 outputs , and continuous improvement . In order to analyze and display the results , statistical analysis software Spss was and manual analysis . The search results were: The reality of Agricultural Extension and environment system is weak through Results Reached by researcher .The majority of the respondents agreed to the proposed concept To improve the quality system composed of agricultural inputs , processes , outputs , and continuous improvement There are variations in the importance of axes and paragraphs of environmental Agricultural extension system in the provinces of Central region of Iraq , but these were minor variation which indicates that most of them were important The researcher reached the following recommendations .And the need to form a joint committee between the ministries concerned with the environment and improve the exchange of information